My learning portfolio / Ruqayyah Ismail … [et al.] - Ismail, Ruqayyah; Ahmad, Hazrina; Abdul Karim, Nurulzatushima; Wahid, Norlizan; Ahmad Zakwan, Fariz Aswan (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
'My Learning Portfolio' is an online student portfolio that can be utilized by students to record their academic and extra-curricular activities throughout their studies in the university. This paperless user friendly online system is a blog lookalike and it gives students the opportunity to share their views and document their activities wherever they are even off campus. This system not only benefits the university but it also the students since they will have a proper documentation of activities that can be used in their resume. This online system permits them to use the URL address as reference to the information rather than having to print out the whole document to submit their job application.